Ionized gas kinematics of cluster AGN at z ∼ 0.8 with KMOS. Issue 1 (16th June 2021) - Paillalef, Marcela G; Flores, Hector; Demarco, Ricardo; Rettura, Alessando; Jaffé, Yara; Lidman, Chris; Nantais, Julie; Puech, Mathieu; Rosati, Piero
ABSTRACT: We present an integral field spectroscopy study of two active galactic nuclei (AGN) in the galaxy cluster RXJ0152–137 at z = 0.84. We have combined integrated and 3D spectra with HST images to perform a complete morpho-kinematical analysis of each galaxy. For G557, we detect narrow and broad H α and [N ii ] emission. The broad H α component is redshifted by v ∼ 939 km s −1 concerning the narrow component. The kinematics analysis and VLT/FORS2 data indicate that G557 presents evidence of radial outflows. For G300, it was possible to detect only the broad H α emission. The spectral properties of both galaxies are equivalent to those of local AGN. We also compare the results obtained for each AGN with their location within the cluster. We found a possible connection of the environment with the properties inferred for each of them, and the possible interaction of G557 with an unconfirmed neighboring galaxy, for which a bridge-like structure is observed in the HST images. This work shows evidence of how the same type of AGN can show differences in their spectroscopic properties depending on the region of the cluster in which they develop, which is important to understand how the environment affects AGN and, consequently, the evolution of galaxies.